Dual-wavelength vortex beam with high stability in a diode-pumped Yb:CaGdAlO4 laser. (26th March 2018) - Shen, Yijie; Meng, Yuan; Fu, Xing; Gong, Mali
Abstract: We present a stable dual-wavelength vortex beam carrying orbital angular momentum (OAM) with two spectral peaks separated by a few terahertz in a diode-pumped Yb:CaGdAlO4 (CALGO) laser. The dual-wavelength spectrum is controlled by the pump power and off-axis loss in a laser resonator, arising from the broad emission bandwidth of Yb:CALGO. The OAM beam is obtained by a pair of cylindrical lenses serving as a π / 2 convertor for high-order Hermite–Gaussian modes. The stability is verified by the fact that a 1 ħ OAM beam with two spectral peaks at 1046.1 nm and 1057.2 nm (3.01 THz interval) can steadily operate for more than 3 h. It has great potential for scaling the application of OAM beams in terahertz spectroscopy, high-resolution interferometry, and so on.